Rapid and accurate identification of Escherichia coli K-12 strains. - Kuhnert, P (1995)
A specific PCR for the identification of K-12 strains, based on the genetic structure of the O-antigen gene cluster (rfb) of Escherichia coli K-12, is described. The assay clearly differentiates E. coli K-12-derived strains from other E. coli strains used in the laboratory or isolated from human and animal clinical specimens, from food, or from environmental samples. Moreover, lineages of K-12 strains can be distinguished with a second PCR based on the same gene cluster. The method presents a useful tool in identifying K-12 for monitoring strains which are used as biologically safe vehicles in biotechnological research, development, and production processes.